2020
DOI: 10.1002/brb3.1790
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological indicators of internal attention: An electroencephalography–eye‐tracking coregistration study

Abstract: We are often looking, but not always seeing, as we spend a considerable amount of time focusing our attention on internal processes (Killingsworth & Gilbert, 2010; Song & Wang, 2012). The term internally directed cognition (IDC; Chun, Golomb, & Turk-Browne, 2011) refers to the devotion of attention to internal information and encompasses a wide range of mental activities

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 94 publications
(187 reference statements)
11
48
0
Order By: Relevance
“…A few studies have begun to address this question by combining neurophysiological methods and eye tracking in the investigation of internal/external attention. In a recent EEG-eye tracking coregistration study (Ceh et al, 2020) that employed the same paradigm as used in Benedek et al (2017), we replicated the finding that IDC is associated with relatively higher posterior alpha power (cf. Benedek et al, 2011Benedek et al, , 2014, and, amongst others, with higher PD.…”
Section: The Relationship Between Eye Behavior and Brain Activation Isupporting
confidence: 70%
See 4 more Smart Citations
“…A few studies have begun to address this question by combining neurophysiological methods and eye tracking in the investigation of internal/external attention. In a recent EEG-eye tracking coregistration study (Ceh et al, 2020) that employed the same paradigm as used in Benedek et al (2017), we replicated the finding that IDC is associated with relatively higher posterior alpha power (cf. Benedek et al, 2011Benedek et al, , 2014, and, amongst others, with higher PD.…”
Section: The Relationship Between Eye Behavior and Brain Activation Isupporting
confidence: 70%
“…Studies comparing eye behavior between EDC and IDC observed differences in a large range of oculometric parameters (Annerer-Walcher et al, 2018;Benedek et al, 2017;Ceh et al, 2020;Walcher et al, 2017). Some of these parameters showed a very uniform pattern, even across different tasks (e.g.…”
Section: Eye-tracking Correlates Of Internal Cognitionmentioning
confidence: 99%
See 3 more Smart Citations